Dose-Rate Effects in Breaking DNA Strands by Short Pulses of Extreme Ultraviolet Radiation - Vyšín, Luděk; Burian, Tomáš; Ukraintsev, Egor; Davídková, Marie; Grisham, Michael E; Heinbuch, Scott; Rocca, Jorge J; Juha, Libor (Radiation research, 2018)
In this study, we examined dose-rate effects on strand break formation in plasmid DNA induced by pulsed extreme ultraviolet (XUV) radiation. Dose delivered to the target molecule was controlled by attenuating the incident photon flux using aluminum filters as well as by changing the DNA/buffer-salt ratio in the irradiated sample. Irradiated samples were examined using agarose gel electrophoresis. Yields of single- and double-strand breaks (SSBs and DSBs) were determined as a function of the incident photon fluence. In addition, electrophoresis also revealed DNA cross-linking. Damaged DNA was inspected by means of atomic force microscopy (AFM). Both SSB and DSB yields decreased with dose rate increase. Quantum yields of SSBs at the highest photon fluence were comparable to yields of DSBs found after synchrotron irradiation. The average SSB/DSB ratio decreased only slightly at elevated dose rates. In conclusion, complex and/or clustered damages other than cross-links do not appear to be induced under the radiation conditions applied in this study.
Keywords: Ultraviolet Rays; zlomy DNA; vztah dávky záření a odpovědi; Plasmids; plazmidy; Dose-Response Relationship, Radiation; DNA Breaks; ultrafialové záření